Radix mesiolingualis and radix distolingualis: a case report of a tooth with an unusual morphology - Gurudutt Nayak; Himanshu Aeran; Inderpreet Singh (Korean Academy of Conservative Dentistry, 2016)
Variation in the root and canal morphology of the maxillary first molars is quite common. The most common configuration is 3 roots and 3 or 4 canals. Nonetheless, other possibilities still exist. The presence of an additional palatal root is rather uncommon and has been reported to have an incidence of 0.06 - 1.6% in varying populations studied. Whenever two palatal roots exist, one of them is the normal palatal root, the other is a supernumerary structure which can be located either mesiolingually (radix mesiolingualis) or distolingually (radix distolingualis). This case report describes successful endodontic treatment of a maxillary first molar with radix mesiolingualis and radix distolingualis. Identification of this variation was done through clinical examination along with the aid of multiangled radiographs, and an accurate assessment of this morphology was made with the help of a cone-beam computed tomography imaging. In addition to the literature review, this article also discusses the epidemiology, classifications, morphometric features, guidelines for diagnosis, and endodontic management of a maxillary first molar with extra-palatal root.